Massive Distance Education: Barriers and Challenges in Shifting to a Complete Online Learning Environment - Yeh, Ching-Yi; Tsai, Chin-Chung (Frontiers in Psychology, 2022)
The global pandemic has dramatically changed how the world functions and impacted all sectors of society including all educational institutions. Government and educators respond with immediate online teaching and learning for all students. Massive distance education has been drawn into the picture to provide nonstop learning in most countries worldwide. This study focuses on examining different orders of barriers educators have encountered during the Covid-19 pandemic. The barriers to massive online teaching and learning included the first-order barrier (technological or external barrier), the second-order barrier (internal barrier or teachers’ and parents’ beliefs), the third-order barrier (design thinking barrier), and the 2.5th order barrier (the classroom management barrier). Both teachers and students are suffering from unstable or limited internet connectivity and it directly hinders students’ rights in the massive online education. Teachers are facing the need for sudden pedagogical redesign while parents are enduring the burden of providing all kinds of support for their children’s online learning at home. Some learners are experiencing videoconferencing fatigue and struggling with overwhelming resources and an excessive amount of technology time. This study also identifies a group of forgotten learners, the videoconferencing refugees, who have limited access to the Internet and lost their learning opportunities. From a global perspective, shifting to massive online education may be possible with all four orders of barriers being overcome.